KNOWLEDGE ATTITUDE AND PRACTICES OF NURSES REGARDING NURSING DOCUMENTATION - HUSSAIN, M; SADDIQUE, H; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
Nursing documentation is a critical component of patient care, yet gaps in knowledge and practices can compromise its effectiveness. This study aimed to assess the knowledge, attitudes, and practices of nurses regarding nursing documentation in a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 155 nurses. Data were collected using a structured questionnaire covering demographic characteristics, knowledge, attitudes, and practices related to nursing documentation. Descriptive and inferential analyses were performed using SPSS version 26. Results: While nurses exhibited positive attitudes toward the importance of nursing documentation, significant gaps were identified in knowledge and practices. Only 25.8% recognized the risks associated with non-standard abbreviations, and 54.2% failed to document significant communications with patients’ families. Nurses with higher qualifications and more years of experience demonstrated better knowledge and adherence to documentation protocols. Conclusion: The findings underscore the need for targeted training programs, institutional support, and standardized guidelines to address gaps in nursing documentation practices. These interventions are crucial for enhancing documentation quality, ensuring continuity of care, and improving patient safety.